Vale do Ipanema: Potential and benefits of indian mustard culture by the beekeeping | Vale do Ipanema: Potencial e benefícios da cultura da mostarda indiana pela apicultura - Verslype, Nina Iris; Caldas, Raphael Miller de Souza; Machado, José (Revista Geama, 2016)
As agriculture is widely linked edaphoclimatic characteristics of a place. In this study, digital terrain modeling (DTM) was performed to precipitation parameters, altitude and temperature Micro region Vale do Ipanema. And then these data were analyzed and compared with the requirements of the brown mustard, in order to verify adaptability indian mustard cultivation and its relation to beekeeping. The districts analyzed were Águas Belas, Buíque, Itaíba, Pedra, Tupanatinga and Venturosa. It was possible to conclude that the micro-region has the ability to develop the cultivation of indian mustard, it is a versatile product with great financial returns, which can help with beekeeping in the region, since it is directly linked to beekeeping, bee is the main pollinator of the crop. The crop of indian mustard, can contribute to the increase bee production and the quality of life in the place.